Le roi philosophe - Gérard Dufour (Mélanges de la Casa de Velázquez, 2008)
To his supporters, Joseph I was the personification of the «philosopher king». Patriots took up the expression, but as a term of derision, claiming that his forte was not philosophy but epicureanism. Looking beyond the stoicism which he evinced in the face of adversity, this article analyses the essential traits of that philosophy, that is the ethical principles according to which Joseph, on the Spanish throne, modelled his conduct and sought to behave as a «friend of men», in keeping with the novel that he had published in 1799, Moïna, and it attempts to distinguish the influences (Queen Julie, the Freemasons) that instilled such an attitude in the Emperor’s brother.